High Prevalence of ST131 Subclades C2-H30Rx and C1-M27 Among Extended-Spectrum β-Lactamase-Producing Escherichia coli Causing Human Extraintestinal Infections in Patients From Two Hospitals of Spain and France During 2015 - Flament-Simon, Saskia-Camille; García, Vanesa; Duprilot, Marion; Mayer, Noémie; Alonso, María Pilar; García-Meniño, Isidro; Blanco, Jesús E.; Blanco, Miguel; Nicolas-Chanoine, Marie-Hélène; Blanco, Jorge (Frontiers in Cellular and Infection Microbiology, 2020)
The present study was carried out to evaluate the prevalence of sequence type 131 (ST131) among 188 extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) collected in 2015 in Lucus Augusti University hospital (Lugo, Spain) and AP-HP Beaujon hospital (Clichy, France) with regard to other STs and to characterize, the types of ESBL produced, serotypes, virulence factor (VF)-encoding genes and the ST131 clades and subclades. ST131 was detected in 33 (39.1%) and 46 (47.9%) of the isolates in Lucus Augusti and Beaujon, respectively. The 109 remaining isolates displayed 57 other STs, the following STs being displayed by at least three isolates: ST10 (8 isolates), ST23 (3), ST38 (4), ST58 (3), ST88 (5), ST95 (4), ST167 (3), ST354 (5), ST361 (3), ST410 (6), ST648 (4), ST744 (3), and ST1615 (6). ST354, ST410, and ST1615 were significantly (P < 0.05) more frequent in Lucus Augusti (5.4%, 6.5%, and 6.5%) than in Beaujon (0% for the three STs). The new globally emerging clone ST1193 among extraintestinal clinical ESBL-EC was identified in one isolate from France and one from Spain. CTX-M-15 was the commonest ESBL detected in the two hospitals (44.6% in Lucus Augusti and 50.0% in Beaujon). CTX-M-14 was significantly (P = 0.0003) more frequent in Lucus Augusti (31.5%) than in Beaujon (10.4%), whereas CTX-M-1 (20.8 vs. 7.6%; P = 0.008) and CTX-M-27 (15.6 vs. 6.5%; P = 0.0389) were more frequent in Beaujon than in Lucus Augusti. The ST131 isolates showed a higher virulence score (mean 13.367) compared with the non-ST131 isolates (mean 7.661) (P < 0.001). Among the 79 ST131 isolates, most of them (52; 65.8%) belonged to subclade C2 (also known as subclone H30Rx) followed by those belonging to subclade C1 (cluster C1-M27: 16 isolates, 20.3%; cluster non-C1-M27: 6 isolates, 7.6%) and clade A (4 isolates; 5.1%). The C2 subclade isolates showed a higher VF-encoding gene score (mean 14.250) compared with the C1-M27 cluster isolates (mean 10.875) (P < 0.001). In conclusion, this study highlights the epidemiological differences between the ESBL-EC isolated from two hospitals of France and Spain obtain in 2015 and reports, for the first time, the presence of clone ST1193 in Spain.